Postnatal Expression Profile of MicroRNAs Associated with Cardiovascular Diseases in 3- to 11-Year-Old Preterm-Born Children - Hromadnikova, Ilona; Kotlabova, Katerina; Krofta, Ladislav; Sirc, Jan (Biomedicines, 2021)
(1) Background: Preterm-born children have an increased cardiovascular risk with the first clinical manifestation during childhood and/or adolescence. (2) Methods: The occurrence of overweight/obesity, prehypertension/hypertension, valve problems or heart defects, and postnatal microRNA expression profiles were examined in preterm-born children at the age of 3 to 11 years descending from preterm prelabor rupture of membranes (PPROM) and spontaneous preterm birth (PTB) pregnancies. The whole peripheral blood gene expression of 29 selected microRNAs associated with cardiovascular diseases was the subject of our interest. (3) Results: Nearly one-third of preterm-born children (32.43%) had valve problems and/or heart defects. The occurrence of systolic and diastolic prehypertension/hypertension was also inconsiderable in a group of preterm-born children (27.03% and 18.92%). The vast majority of children descending from either PPROM (85.45%) or PTB pregnancies (85.71%) had also significantly altered microRNA expression profiles at 90.0% specificity. (4) Conclusions: Postnatal microRNA expression profiles were significantly influenced by antenatal and early postnatal factors (gestational age at delivery, birth weight of newborns, and condition of newborns at the moment of birth). These findings may contribute to the explanation of increased cardiovascular risk in preterm-born children. These findings strongly support the belief that preterm-born children should be dispensarized for a long time to have access to specialized medical care.
Keywords: birth weight of newborns; gestational age at delivery; microRNA; whole peripheral blood; condition of newborns at the moment of birth; children; preterm prelabor rupture of membranes; cardiovascular risk; spontaneous preterm birth; expression